2012
DOI: 10.1042/bj20111881
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate is not an absolute requirement for the inhibitory effects of cyclosporin A or cyclophilin D deletion on mitochondrial permeability transition

Abstract: CypD (cyclophilin D) has been established as a critical regulator of the MPT (mitochondrial permeability transition) pore, and pharmacological or genetic inhibition of CypD attenuates MPT in numerous systems. However, it has recently been suggested that the inhibitory effects of CypD inhibition only manifest when Pi (inorganic phosphate) is present, and that inhibition is lost when Pi is replaced by Asi (inorganic arsenate) or Vi (inorganic vanadate). To test this, liver mitochondria were isolated from wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
3
6
2
Order By: Relevance
“…However, pore regulation by P i has recently been reappraised, as the entire regulatory action of CypD, and thereby CsA, has been suggested to be P i dependent (38). However, this hypothesis is in direct contrast to a recent report by Baines et al in which P i had absolutely no effect in Ppif null or CsA-inhibited pore opening (74), a result that is supported by results from Halestrap’s group who found that P i actually enhanced MPTP opening, but independent of CsA (73). Despite the potential effect of P i , the PiC itself has been suggested to be either an effector of the MPTP, or possibly even a structural component (75).…”
Section: Phosphate Carrier (Pic)contrasting
confidence: 79%
“…However, pore regulation by P i has recently been reappraised, as the entire regulatory action of CypD, and thereby CsA, has been suggested to be P i dependent (38). However, this hypothesis is in direct contrast to a recent report by Baines et al in which P i had absolutely no effect in Ppif null or CsA-inhibited pore opening (74), a result that is supported by results from Halestrap’s group who found that P i actually enhanced MPTP opening, but independent of CsA (73). Despite the potential effect of P i , the PiC itself has been suggested to be either an effector of the MPTP, or possibly even a structural component (75).…”
Section: Phosphate Carrier (Pic)contrasting
confidence: 79%
“…Mouse liver mitochondria were isolated and assayed for PTP opening under energized and de-energized conditions using Dr. Baines’ established protocols 32 . Briefly, 0.25mg/mL mitochondria were placed in swelling buffer containing (in mM) 120 KCl, 10 Tris/HCl, and 5 KH 2 PO 4 (pH 7.4), with (energized) or without (de-energized) 5 succinate (separate pilot experiments with glutamate/malate yielded similar results).…”
Section: Methodsmentioning
confidence: 99%
“…4,5 The mechanisms whereby CypD deficiency prevents MPTP activation are under investigation and not established yet. 6 - 8 …”
mentioning
confidence: 99%